PERUMPAMAAN TENTANG ORANG KAYA DAN LAZARUS YANG MISKIN:: SEBUAH KAJIAN TENTANG KEHIDUPAN SETELAH KEMATIAN - Lola, James A.; Marumbona, Arung P.; Juprianus (STT-RAI Batam, 2024)
The parable of the rich man and Lazarus recorded in Luke 16:19-31 has been the subject of much attention and commentary among Christians and is one of the most debated parables of Jesus. One of the issues of debate regarding this parable is related to the meaning and intentions of the afterlife. This study aims to answer the question of life after death by using a qualitative research method with a hermeneutic approach. Thus, the result of this study is that life after death is something that really exists. Placing humans in two places, namely the bosom of Abraham and Hades, where the place in life after death is determined by life in the world today. Everyone believes that at the end of all history, Jesus will return to judge all people according to their deeds, even the dead will be resurrected, and through the judgment, the righteous will be given the blessing of eternal life and the wicked will be punished in eternal punishment.